Leadership in Righteous Service - Hanapia, Cepi; Muliasutisna, Asep; Purwanto, Purwanto; Rahmatulloh, Aang; Upa, Fatmawati Pua (Universitas Pahlawan Tuanku Tambusai, 2024)
Humans are monodualistic beings who have roles as individuals and social beings. As individuals, humans are given the intellect, thoughts, and feelings to develop themselves and meet their life needs independently. As social beings, humans live in society, nation, and state, so they need each other. In modern society, various organizations have emerged, including government organizations that according to the political trias consist of the legislature, executive, and judiciary. At the highest executive level there is a president, while at the village level there is a village head. The Village Head, who is democratically and traditionally elected, plays an extension of the community to regulate, maintain, and motivate residents in the development process. The success of village development is highly dependent on the leadership of the Village Head in mobilizing community participation. As God's creatures with the highest degree, humans have the responsibility as caliphs on earth to maintain the balance and continuity of life. In everyday life, the essence of human beings as individuals and social beings is obvious; When faced with difficulties, human beings need the help of others, while in personal affairs, they tend to maintain privacy as a form of individuality. This balance between individual and social roles is the basis for the progress of society, including at the village level, where cooperation between leaders and citizens is the key to the success of sustainable development.